Rys biograficzny Józefa Kwiatka – kierownika Katedry Pedagogiki Uniwersytetu Poznańskiego w latach 1953–1961 - Nowak-Kluczyński, Konrad (Biuletyn Historii Wychowania, 2026)
The article is an attempt to reconstruct the educational, academic path of Józef Kwiatek, a Polish pedagogue and sociologist affiliated with the Adam Mickiewicz University in Poznań. This is an outline of teaching, organizing and research activities based on a chronological arrangement, with a simultaneous thematic arrangement that takes into account the changing organizational structure of higher education, as well as the historical context. Józef Kwiatek became known as a committed teacher and social and political activist. He was the head of the Department of Pedagogy at the University of Poznan from 1953 to 1961, while also serving as UAM’s pro-rector for teaching in recognition of his great organizational experience. He headed the Poznań Pedagogical Society, of which he became an honorary member.